2016
DOI: 10.1111/ejn.13417
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia reduces discharge rates in the human pallidum without changing the discharge rate ratio between pallidal segments

Abstract: Classical rate models of basal ganglia circuitry associate discharge rate of the globus pallidus external and internal segments (GPe, GPi respectively) solely with dopaminergic state and predict an inverse ratio between the discharge rates of the two pallidal segments. In contrast, the effects of other rate modulators such as general anesthesia (GA) on this ratio have been ignored. To respond to this need, we recorded the neuronal activity in the GPe and GPi in awake and anesthetized human patients with dyston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Moreover, we recorded the pallidal activity in anesthetized animals. Earlier studies demonstrated that anesthesia reduces the discharge rate of the GPe neurons (e.g., Castrioto et al., 2016). Therefore, we cannot rule out the possibility that anesthesia regimen minimized the DREADD’s action/CNOs'effect on pallidal activity.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, we recorded the pallidal activity in anesthetized animals. Earlier studies demonstrated that anesthesia reduces the discharge rate of the GPe neurons (e.g., Castrioto et al., 2016). Therefore, we cannot rule out the possibility that anesthesia regimen minimized the DREADD’s action/CNOs'effect on pallidal activity.…”
Section: Discussionmentioning
confidence: 94%
“…The potential impact of nitrous oxide on MER was not discussed. 26 In summary, the evidence on the effects of volatile anesthetics on MER consists of 8 clinical trials with small sample sizes in which different volatile anesthetic agents and different surgical targets were investigated. Because of this heterogeneity in disease states, targets, and anesthetic agents, it is difficult to draw definitive conclusions on the effects of volatile anesthesia on MER.…”
Section: Volatile Anesthetic Agentsmentioning
confidence: 99%
“…Chen et al also reported that there was no difference in the UPDRS III reduction rate and score 6 months after STN DBS surgery between the MER group and the non-MER group [42]. In addition to frequently used imaging sequences, direct targeting can be used with quantitative susceptibility mapping (QSM) and diffusion tensor imaging (DTI) [ GA with both volatile and intravenous anesthetics in PD and dystonia patients showed no significant difference compared with patients awake during the procedure [54,[88][89][90][91]. Notably, the neural activity of typical burst pattern disappeared when higher anesthetic doses were used.…”
Section: Is Mer Mandatory For Stn Dbs Surgery?mentioning
confidence: 99%
“…The biggest concern with STN DBS surgery under GA for movement disorder is the possibility of diminution of MER signals. A few small-sized retrospective studies have reported that MER obtained from STN, GPi, substantia nigra in STN DBS surgery under GA with both volatile and intravenous anesthetics in PD and dystonia patients showed no significant difference compared with patients awake during the procedure [ 54 , 88 , 89 , 90 , 91 ]. Notably, the neural activity of typical burst pattern disappeared when higher anesthetic doses were used.…”
Section: Stn Dbs Using Intraoperative Imaging or Microelectrode Rementioning
confidence: 99%